Molecular data and premilinary phylogeny of several paradoxosomatid millipede species in Vietnam (Diplopoda: Polydesmida: Paradoxosomatidae) - Anh, Nguyen Duc; Son, Nguyen Giang (Academia Journal of Biology, 2016)
The paper provides new data on molecular sequences of 10 millipede species of the family Paradoxosomatidae Daday, 1889 from Vietnam. A 680 bp fragment of the mitochondrial gene COI was sequenced, and registered in GenBank with accession numbers. Similarity matrix and genetic distance (p-distance) were calculated using the computer software MEGA 6.0. The aligned dataset of the gene COI consists of 571 bp from 14 samples of 11 species including an outgroup, Polydesmus denticulatus (C.L. Koch, 1847). Genetic distance and similarity matrix clearly show the separation between the family Polydesmidae and members of the family Paradoxosomatidae. P-distance values among paradoxosomatid species range from 0.063 to 0.236. Almost all p-distance values of Polydesmus denticulatus with other paradoxosomatid species are higher than 0.2. Among same species, p-distance values are also variable from 0.047 for Sellanucheza grandis, 0.063 for Tonkinosoma flexipes, and relatively high (0.102) for Tonkinosoma jeekeli. The phylogenetic trees were reconstructed using two methods: Maximum Likelihood and Bayesian Inference. Both ML and BI trees support the separation of the tribe Chamberlinini from other species. The relationship among other taxa, Tonkinosomatini, Sulciferini and Orthomorphini is unsolved due to limitations of molecular data and samples. In addition, the taxonomic position of the species Tonkinosoma jeekeli is recommended to revise.